REF6 promotes lateral root formation through de‐repression of PIN1/3/7 genes. Issue 4 (2nd December 2018) - Wang, Xiaolei; Gao, Jiong; Gao, Shan; Li, Zhongpeng; Kuai, Benke; Ren, Guodong
Summary: The H3K27 methyltransferase CLF inhibits lateral root (LR) formation through depositing the repressive H3K27me3 mark to the chromatin of PIN1, a key polar auxin transporter gene. Here, we show that the H3K27me3 demethylase REF6 promotes lateral root primordium initiation and LR emergence. REF6 directly binds to the chromatin of PIN1/3/7 . Dysfunction in REF6 results in increased levels of H3K27me3 on PIN1/3/7 and suppressed expression of PIN genes. Genetic analysis of the clf ref6 double mutant revealed an antagonistic action between CLF and REF6, in terms of LR formation. Our findings indicate that H3K27 methylation and demethylation activities are likely coordinated to ensure proper LR organogenesis. Abstract : CLF and REF6 are "writer" and "eraser" enzymes of the H3K27 methylation mark, respectively. In this study, we reported that REF6 promotes lateral root formation through de‐repression of PIN 1/3/7, the polar auxin transporter genes, by antagonizing CLF activities.